Muhammad is the Messenger of God, may God bless him and grant him peace: In the divine books - Amin, Abdulkarim Fattah; Agha Baba, Awat Muhammad; Ibrahim, Shamal Ahmed; Kamal Al-Din, Nabaz Jamal; Hama Gharib, Bahra Salam (Universitas Islam Negeri Raden Intan Lampung, 2022)
Through the preparation of our research, we were able to show many and abundant results and we cannot return them, but to make it easier for the dear reader, we talk to you about a summary of it in the following points: We divided our research into two topics: The first topic: Muhammad is the Messenger of God in the Torah and the Bible and the Qur'an, and this title contains three demands, and the second topic: Muhammad is the Messenger of God in the semi-celestial books: the Kazanpura and the sacred books of Hinduism and Avista, as well as this topic as its predecessor contains three demands. It is worth noting: We brought in the three demands the texts of these heavenly books towards our Messenger Muhammad - may God’s prayers and peace be upon him - that negate the suspicion, and which we like that the texts of these books are very close to the Seal of the Prophets and the Messenger - peace be upon them. • The noble reader warned us that the texts of the Torah and the Gospel have been subjected to distortion from two aspects: the first: deleting some texts altogether, and the second: distorting its meaning and carrying it to another meaning. • Also, in the three demands of the second topic, we brought the texts of Kaspara, Avista, and the sacred books of Hinduism towards the Messenger - may God bless him and grant him peace - and we learned from those texts that these three religions are concerned with the Prophet of Islam and his Messenger, our master Muhammad - may God bless him and grant him peace - and consider it with consideration. • And we named the second topic: Muhammad, the Messenger of God, in the semi-heavenly books: Kazanbara and the sacred books of Hinduism, for the sake of the fact that those books were not descended from God Almighty and on this view the masses of Muslim scholars went almost to reach an agreement.